Rip Current Hazard in Klayar Beach, Pacitan, Indonesia: Inferred from Fluorescent Dye and UAV - Wahyudi; Hendy Fatchurohman; Verent Priscillia Rahayu Natasya; Sujantoko; Leo Eliasta Sembiring (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
South coasts of Java have a unique landscape that exhibits exotic and phantastic natural view which is very attractive as tourist destinations. Therefore, coastal tourism potential in this area is very promising. Despite the fascination of such areas, the existence of rip current in the beach can be very hazardous to the visitors. Klayar Beach (KB) is one of the most popular recreational beaches in Pacitan Regency, East Java Province, Indonesia. However, KB poses a hazard due to rip currents. This paper presents the result of field observations of rip currents utilizing fluorescent dying and unmanned aerial vehicle (UAV). We used UAV multirotor DJI Mavic 2 Zoom with video camera to take and monitor aerial photo and video of rip current flows. The result of this study proves that there is rip currents in KB. It also reveals that the maximum velocity reaches 0.8 m/s, with average width of 11 m, and total length 99.99 m. The rip current type in the KB is defined as headland boundary controlled and predicted as a permanent rip. The use of combined uranine and UAV to investigate rip current in this study was a very effective way. It is suggested to use this approach to improve people understanding about rip current hazard for promoting beach safety.